Penyuluhan Kehamilan Berisiko Tinggi Pada Ibu Hamil Di Bontoa - Nur Ismi Wahyuni (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2023)
High risk pregnancy is a pregnancy that causes greater harm and complications to the mother and fetus during pregnancy, childbirth or postpartum when compared to normal pregnancy, childbirth and postpartum. One of the reasons for the high MMR is because pregnant women who are at risk were not detected early. Complications that can occur from risky pregnancies are antepartum bleeding, prolonged labor, prematurity, low birth weight (LBW). A risk pregnancy is an abnormal pregnancy that can affect the health of the mother and fetus. Sustainable development Sustainable Development Goals (SDGs), one of the targets that can be measured is a reduction in the Maternal Mortality Rate (MMR). This activity was carried out in Ampekale Village, Bontoa District, Maros Regency using the method of providing counseling to pregnant women in turn using brochures which were distributed to each pregnant mother, after which a question and answer session was held and screening was carried out to detect pregnant women who were in the high risk group. This activity was attended by 24 pregnant women. This community service provides good benefits, namely gaining knowledge about increasing pregnant women's knowledge about high-risk pregnancies in pregnant women as well as ways to prevent and anticipate danger signs of pregnancy in high-risk pregnancies.